The encyclopedia of mosaic techniques - Biggs, Emma (Search Press, 2015)
This complete guide brings to life the ancient art of creating beautiful mosaics. Transform your pottery, furniture, walls, and floors with fabulous mosaics and learn foolproof techniques for coordinating colour choices to produce dynamic designs. Use a wide range of tessarae, from traditional ceramic tiles to pebbles, broken pottery and other found objects." -- Provided by publisher